Nanoplastics formed during the mechanical breakdown of daily-use polystyrene products. Issue 3 (12th December 2018) - Ekvall, Mikael T.; Lundqvist, Martin; Kelpsiene, Egle; Šileikis, Eimantas; Gunnarsson, Stefán B.; Cedervall, Tommy
Abstract : Limited mechanical force produces plastic nanoparticles from commonly used plastic objects. Abstract : Large amounts of plastics are released into the environment every day. These released plastics have a clearly documented negative effect on wildlife. Much research attention has been given to large plastic pieces and microplastics. However, if the breakdown of plastics is a continous process, eventually nanoplastics will be produced. Nanoplastics will affect wildlife differently from larger plastic pieces. We have studied the products formed by the mechanical breakdown of two commonly used polystyrene products, takeaway coffee cup lids and expanded polystyrene foam. After breakdown using a food processor, we characterized the breakdown products using seven different methods and found nanosized polystyrene particles with different shapes and negative or nearly neutral surface charges. These results clearly demonstrate that daily-use polystyrene products can break down into nanoparticles. Model polystyrene particles with different sizes and surface modifications have previously been shown to have different negative effects on wildlife. This indicates that breakdown nanoparticles might have the potential to cause cocktail effects in nature.